Postfeminist Gothic
X, 189 p.
Keywords: This book explores new critical ground by addressing the intersection of two contentious concepts, postfeminism and Gothic. This collection of original and exciting essays examines a number of Gothic texts, from Anne Radcliffe's romances to modern horror films, in conjunction with diverse postfeminist theories, from backlash to postmodern feminism.